Shrimp immune response: A transcriptomic perspective. (5th December 2021) - Fajardo, Carlos; Martinez‐Rodriguez, Gonzalo; Costas, Benjamin; Mancera, Juan Miguel; Fernandez‐Boo, Sergio; Rodulfo, Hectorina; De Donato, Marcos
Abstract: During the last 15 years, a significant amount of data related to the crustacean immune system has been generated, mainly led by the advances made in the field of transcriptomic analysis through massive mRNA sequencing technology. In order to shed new light on the genes and metabolic pathways associated with the immune system in shrimp species, we have carried out a meta‐analysis using the current literature and the Sequence Read Archive (SRA) database of the National Center for Biotechnology Information (NCBI), which has 1195 published transcriptomic data sets until 31 December 2020, from different tissues and 14 Penaeus species. The transcriptomic analyses published so far have explored the effects of the challenge from viral and bacterial pathogens, as well as abiotic stressors, such as ammonia, temperature, salinity, oxygen deprivation and pH. They have also explored the effect of dietary factors and beneficial microbes (pre‐ and probiotics) in the immune response. In order to harness the vast amount of information available, multidisciplinary efforts have to generate better genomic tools to overcome the complexity of the genome and to implement the knowledge gained into commercial applications for the improvement of the culture conditions, adaptation of more sustainable feeds and producing strains showing more resilience/tolerance to diseases.